2002
DOI: 10.1021/ef010233r
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Microstructure of Bitumen and Its Fractions by Modulated Differential Scanning Calorimetry

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
117
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 18 publications
12
117
0
Order By: Relevance
“…With this regard, bitumen is well known to be a multiphase system mainly composed of two fractions: maltenes (which include three different families of compounds: saturates, aromatics and resins) and asphaltenes. According to Masson and co-workers [32,33], they order in four stages upon cooling from melt, yielding four specific thermal events in the non-reversing heat flow curve. The analysis of the fourth thermal event may provide an approximate idea on changes occurred at a microstructural level.…”
Section: Chemical Modification and Microstructurementioning
confidence: 99%
“…With this regard, bitumen is well known to be a multiphase system mainly composed of two fractions: maltenes (which include three different families of compounds: saturates, aromatics and resins) and asphaltenes. According to Masson and co-workers [32,33], they order in four stages upon cooling from melt, yielding four specific thermal events in the non-reversing heat flow curve. The analysis of the fourth thermal event may provide an approximate idea on changes occurred at a microstructural level.…”
Section: Chemical Modification and Microstructurementioning
confidence: 99%
“…6,7 The segregation being time dependent, it was suggested that the formation of the mesophase was responsible for the steric hardening of bitumen. This communication provides evidence of this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, above the frozen state defined by T > Tg, molecular mobility increases and those saturates segments order into crystalline domains [22,23,25]. Table 2, which displays second event temperatures (T2nd) confirms a decrease after addition of 9 wt.% Th and 60 days of curing, as the frozen state threshold was shifted to lower temperatures.…”
Section: On the Chemistry Behind Bitumen Modification Via Thioureamentioning
confidence: 68%
“…8B presents two welldefined peaks (with peak maximum, Tg1 and Tg2, located at -30.5 and 3.0 ºC, respectively) which, according to Masson et al [22,23], derive from two overlapped glass transitions corresponding to saturates and aromatics. Tg2 values were also determined for the modified binders studied, and compare with neat bitumen's.…”
Section: On the Chemistry Behind Bitumen Modification Via Thioureamentioning
confidence: 90%
See 1 more Smart Citation